Recurrence of severe duodenal disease after endoscopic downstaging in familial adenomatous polyposis. (13th March 2011) - Balmforth, D; Neale, K; Clark, S; Phillips, R
Abstract : Introduction: Duodenal polyposis is found in the majority of patients with familial adenomatous polyposis. Endoscopic surveillance programmes grade the severity of duodenal disease according to the Spigelman classification (stages 0–IV) to identify patients at risk of developing adenocarcinoma. Duodenoscopy can also be used therapeutically to remove polyps and thus reduce a patient's Spigelman stage. This study aims to evaluate the progression of duodenal polyposis in patients with a previous diagnosis of Spigelman stage IV disease who have been downstaged by endoscopic or pharmacological means. Methods: This retrospective cohort study used a database search of a large prospective polyposis registry to identify patients who had been downstaged from stage IV disease and had further opportunity for disease progression. These patients were divided into three groups according to their new Spigelman stage. A measure of a patient's disease progression was obtained by the increase in stage over the recommended follow-up time period for their new, reduced, Spigelman stage. Results: A total of 41 patients were indentified. Group 1 (n = 16) were downstaged to stage III disease, with 50% progressing back to stage IV over the recommended 1-year follow-up period. Group 2 (n = 19) were downstaged to stage II disease, with 84% undergoing progression over the recommended 3-year follow-up period. Group 3 (n = 6) were downstaged to stage I disease, with 100% undergoing progression over the recommended 5-year follow-up period. No patients were downstaged to stage 0. Conclusion: Patients downstaged from Spigelman stage IV demonstrate an increased rate of disease progression back to severe disease in comparison to reported rates of primary disease progression. An amendment to the current endoscopic surveillance protocol is recommended to ensure that once a patient has been classified as having stage IV disease they are treated as a high-risk patient in perpetuity.